Negotiating climate change as a social situation - Wietze Lise; Richard S. J. Tol; Bob van der Zwaan (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper applies the theory of social situations to international environmental agreements on greenhouse gas emission reduction. The usual pessimism on the size of stable coalitions among world regions is challenged for two alternative cases, namely by introducing farsightedness and by introducing coalitional moves with commitment. This is an extension of stability in the cartel game, where a cartel symbolises a coalition among world regions for reducing greenhouse gas emissions. It is a special case of the commitment situation, which has been proposed in the theory of social situations. The results are obtained by restricting the move rules in the game among world regions.
Keywords: C7; F42; Q2; 330; Coalitions; coalitional moves; cooperation; theory of social situations; international negotiations; climate change; Klimaschutz; Internationale Umweltpolitik; Verhandlungen; Theorie; Nichtkooperatives Spiel